Chinese reality shows: national features and innovations - Li Zheng (Journal of the Belarusian State University. Journalism, 2022)
The article analyses reality TV as one of the most popular forms of Chinese entertainment TV show. It is an integral element of entertainment television characterised by features that distinguish this form from other types of shows. The article examines the impact of reality shows from perspectives of spiritual and moral culture of the modern Chinese audience. The particularity of Chinese reality shows reflects the innovation of Chinese entertainment TV content.